Sintering parameters and mechanical properties of injection moulded aluminium powder - (:unkn) unknown (MANEY PUBLISHING, 2011)
This paper describes the microstructural and mechanical properties of injection moulded aluminium powder. Gas atomised aluminium powder was injection moulded with wax based binder. The critical powder loading for injection moulding was 62.5 vol.-% for feedstock. Binder debinding was performed in solvent and thermal method. After debinding, the samples were sintered at different temperatures and times in high purity N(2). Metallographic studies were conducted to determine the extent of densification and the corresponding microstructural changes. The results show that gas atomised aluminium powder could be sintered to a maximum 96.2% of theoretical density. Maximum density, tensile strength and hardness were obtained when sintered at 650 degrees C for 60 min.
Keywords: Powder injection moulding; Sintering; Aluminium; MATRIX COMPOSITES; BEHAVIOR